1986
DOI: 10.1073/pnas.83.13.4646
|View full text |Cite
|
Sign up to set email alerts
|

The pH dependence of the mechanism of reaction of hydrogen peroxide with a nonaggregating, non-mu-oxo dimer-forming iron (III) porphyrin in water.

Abstract: The pH dependence of the mechanism of reaction of hydrogen peroxide with a nonaggregating, non-,R-oxo dimer-forming iron(HI) porphyrin in water ( Contributed by Thomas C. Bruice, March 3, 1986 ABSTRACT The reaction of hydrogen peroxide with 5, 10,15,20-tetrakis(2,6-dimethyl-3-sulfonatophenyl)porphinatoiron(Il) hydrate [(P)Fem(H20)] has been investigated in water between pH 1 and pH 12. The water-soluble (P)Fe"'(H20) neither aggregates nor forms a ,.-oxo dimer. The pH dependence and rate-limiting second-orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…ROI in these cells is normally inactivated by oxidized glutathione [40] or catalase [41]. This suggests that similar to NAMI-A, ruthenium(III) compound binds preferentially to proteins at low concentration [20] and binds also to nucleobases only at high concentrations [22,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ROI in these cells is normally inactivated by oxidized glutathione [40] or catalase [41]. This suggests that similar to NAMI-A, ruthenium(III) compound binds preferentially to proteins at low concentration [20] and binds also to nucleobases only at high concentrations [22,24].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that this compound presents lower tumor cytotoxic activity when compared with other organic ruthenium(III) compounds [33][34][35][36][37][38][39][40][41][42][43][44][45], but higher cytotoxicity than NAMI-A and derivatives [25,28,36]. Results from previous experiments [44] in which mice transplanted with sarcoma 180 cells were treated with the same ruthenium(III) complex at different time intervals and concentrations revealed that cis-[RuCl2(NH3)4]Cl is remarkably well tolerated in therapeutic doses with little or no toxicity in the host.…”
Section: Discussionmentioning
confidence: 99%
“…To explore whether pH affects generation of different active intermediates at different pHs, we chose 2,2′-azino-bis(3-ethylbenzthiazoline-6-sulphonic acid) (ABTS) as a probe because it is commonly applied for the quantification of the enzymatic activity of peroxidases, and because it serves to trap any hypervalent metal porphyrin[45-47] or Salen species[48, 49]. The experiments for pH-dependent ABTS oxidation were carried out in the presence of H 2 O 2 at 25°C with the ratio of the [catalyst]: [H 2 O 2 ]: [ABTS] being 2.5 μM: 250 μM: 250 μM (1: 100: 100), and the k obs was obtained by monitoring the change of absorption at 734 nm.…”
Section: Resultsmentioning
confidence: 99%
“…It is explained that the lifetime of the Fe 3ϩ -OOH species in heme peroxidases is short, because the distal His becomes an unstable imidazolium cation after accepting a proton from H 2 O 2 at the N⑀ site because of the conserved Asn residue (Asn-70 in HRP), stabilizing the N␦ proton (19ϳ21). We suggest that the O-O bond heterolysis in heme peroxidases is more likely approximated by a 1,2-proton shift from the inner to outer oxygen assisted by the distal His acting as the base catalyst (42).…”
Section: Discussionmentioning
confidence: 99%